Health risk for athletes at moderate altitude and normobaric hypoxia - Schommer, K.; Menold, E.; Subudhi, A. W.; Bärtsch, P. (British Journal of Sports Medicine, 2012)
Altitudes at which athletes compete or train do usually not exceed 2000-2500 m. At these moderate altitudes acute mountain sickness (AMS) is mild, transient and affects at the most 25% of a tourist population at risk. Unpublished data included in this review paper demonstrate that more intense physical activity associated with high-altitude training or mountaineering does not increase prevalence or severity of AMS at these altitudes. These conclusions can also be extended to the use of normobaric hypoxia, as data in this paper suggest that the severity of AMS is not significantly different between hypobaric and normobaric hypoxia at the same ambient pO2. Furthermore, high-altitude cerebral or pulmonary oedema do not occur at these altitudes and intermittent exposure to considerably higher altitudes (4000-6000 m) used by athletes for hypoxic training are too short to cause acute high-altitude illnesses. Even moderate altitude between 2000 and 3000 m can, however, exacerbate cardiovascular or pulmonary disease or lead to a first manifestation of undiagnosed illness in older people that may belong to the accompanying staff of athletes. Moderate altitudes may also lead to splenic infarctions in healthy athletes with sickle cell trait.